UNDERSTANDING IDEA OF CURRICULUM 2013 AND ITS CONSISTENCY ON DEVELOPING CURRICULUM DOCUMENT AT LEVEL OF EDUCATION UNIT (KTSP) AT PRIMARY SCHOOL LEVEL - Prihantini, Prihantini (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract:. This study is based on various issues of Curriculum 2013, both in terms of teacher readiness to accept the Curriculum 2013, an understanding of the idea of Curriculum 2013, as well as in the implementation of teaching and learning. In the curriculum development theory, curriculum ideas are an important component that the curriculum development team needs to understand, so that the development of curriculum documents composed reflects continuity with curriculum ideas. The purpose of this study is to describe and explore the understanding of principals and teachers about the idea of Curriculum 2013 and its consistency on developing Education Unit Level Curriculum (KTSP) at elementary school in Sukalarang sub-district, Sukabumi regency. The research method applied is qualitative research with descriptive exploratory approach. The conclusions of the study are: (1) the understanding of principals and teachers about the idea of theÂ  Curriculum 2013 at the know stage, the understanding that curriculum ideas have consistency in the development of the Education Unit Level Curriculum (KTSP) document is not yet owned; (2) the development of KTSP document shows no consistency between the idea of Curriculum 2013 with the documents of Book I KTSP, Book II KTSP, and Book III KTSP; (3) the problems faced by school principals and teachers in relation to the Curriculum 2013 is assessment of learning, both with regard to the techniques and types of assessment and techniques of administering the results of the assessment.Recommendations are proposed to policy makers that training strategies need to be changed from "theory oriented" to "practice oriented" and need to be varied in implementation at the Kecamatan or Cluster levels and enhanced effectiveness of curriculum counseling 2013. For principals and teachers expected to disseminate the 2013 Curriculum should be supported by presenting expert resources during the workshop, Principal Working Group (K3S) and Teachers Working Group (KKG) activities, so that the understanding of the idea of Curriculum 2013 that has not been assessed in training at the Provincial or District level can be strengthened and strengthened during the activities of K3S and KKG.Keyword: Idea of Curriculum 2013, consistency, curriculum development team, KTSP documents, Principal Working Group (K3S), Teachers Working Group (KKG).Â Abstrak: Penelitian ini dilatar belakangi adanya berbagai permasalahan Kurikulum 2013, baik dari sisi kesiapan guru menerima Kurikulum 2013, pemahaman terhadap ide Kurikulum 2013, maupun dalam implementasi pembelajaran. Dalam landasan teori pengembangan kurikulum, ide kurikulum merupakan komponen penting yang perlu dipahami oleh tim pengembang kurikulum, sehingga pengembangan dokumen kurikulum yang disusun mencerminkan kesinambungan dengan ide kurikulum. Adanya sejumlah permasalahan tersebut, maka penelitian ini bertujuan untuk menggambarkan dan meng-eksplorasi pemahaman kepala sekolah dan guru tentang ide Kurikulum 2013 dan konsistensinya terhadap pengembangan dokumen Kurikulum Tingkat Satuan Pendidikan (KTSP) jenjang Sekolah Dasar di Kecamatan Sukalarang Kabupaten Sukabumi. Metode penelitian yang diterapkan adalah penelitian kualitatif dengan pendekatan deskriptif eksploratori. Kesimpulan hasil penelitian adalah: (1) pemahaman kepala sekolah dan guru tentang ide Kurikulum 2013 baru pada taraf kenal dan tahu, pemahaman bahwa ide kurikulum memiliki konsistensi dalam pengembangan dokumen Kurikulum Tingkat Satuan Pendidikan (KTSP) belum dimiliki; (2) dokumen Kurikulum Tingkat Satuan Pendidikan (KTSP) yang dikembangkan menunjukkan tidak ada konsistensi antara ide Kurikulum 2013 dengan dokumen Buku I KTSP, Buku II KTSP, dan Buku III KTSP; (3) permasalahan yang dihadapi kepala sekolah dan guru berkaitan dengan Kurikulum 2013 adalah masalah penilaian, baik berkaitan dengan teknik dan jenis penilaian maupun teknik pengadministrasian hasil penilaian. Rekomendasi diusulkan kepada pengambil kebijakan, bahwa strategi pelatihan perlu diubah dari bersifat â€œtheory orientedâ€ kearah â€œpractice orientedâ€ dan perlu divariasikan pelaksanaannya di tingkat Kecamatan atau Gugus Sekolah serta ditingkatkan efektifitas pola pendampingan Kurikulum 2013. Bagi kepala sekolah dan guru diharapkan dalam mendiseminasikan Kurikulum 2013 perlu didukung dengan menghadirkan nara sumber ahli pada saat kegiatan workshop, kegiatan K3S atau KKG, sehingga pemahaman ide Kurikulum 2013 yang belum terkaji dalam pelatihan di tingkat Provinsi atau Kabupaten dapat diperkuat dan dimantapkan pada saat kegiatan Kelompok Kerja Kepala Sekolah (K3S) dan Kelompok Kerja Guru (KKG).Kata Kunci: Ide Kurikulum 2013, konsistensi, tim pengembang kurikulum, dokumen KTSP, Kelompok Kerja Kepala Sekolah (K3S), Kelompok Kerja Guru (KKG).